Zoonotic Mycobacterium bovis-induced tuberculosis in humans - Maller, B.; Darr, S.; Alonso, Silvia; Hattendorf, J.; Laisse, C.J.M.; Parsons, S.D.C.; Helden, P.D. van; Zinsstag, Jakob (Centers for Disease Control and Prevention, 2013)
We aimed to estimate the global occurrence of zoonotic tuberculosis (TB) caused by Mycobacterium bovis or M. caprae infections in humans by performing a multilingual, systematic review and analysis of relevant scientific literature of the last 2 decades. Although information from many parts of the world was not available, data from 61 countries suggested a low global disease incidence. In regions outside Africa included in this study, overall median proportions of zoonotic TB of ≤1.4% in connection with overall TB incidence rates ≤71/100,000 population/year suggested low incidence rates. For countries of Africa included in the study, we multiplied the observed median proportion of zoonotic TB cases of 2.8% with the continental average overall TB incidence rate of 264/100,000 population/year, which resulted in a crude estimate of 7 zoonotic TB cases/100,000 population/year. These generally low incidence rates notwithstanding, available data indicated substantial consequences of this disease for some population groups and settings.